Impact of additional plasma heating on detached plasma formation in divertor simulation experiments using the GAMMA 10/PDX tandem mirror. (January 2019) - Nakashima, Y.; Islam, M.S.; Iijima, T.; Sakamoto, M.; Ezumi, N.; Yoshikawa, M.; Asakura, N.; Fukumoto, M.; Hatayama, A.; Hirata, M.; Ichimura, M.; Ikezoe, R.; et al.
Highlights: Transition of a detached to attached plasma by ECH in GAMMA 10/PDX tandem mirror. Heat and ion fluxes increased significantly during ECH and with increasing impurity. The impurity ion emission increases remarkably during ECH. Transition characteristics in detached plasmas produced by various radiator gases. N2 seeding has a significant tolerance of sustaining detached plasma during ECH. Abstract: The transition of a detached to attached plasma experiment has been performed in GAMMA 10/PDX by applying an additional plasma heating pulse of electron cyclotron heating (ECH). In a plasma detachment experiment, a short pulse (25 ms) of ECH was applied at the east plug-cell to examine the effects of electron heating on the plasma parameters in the D-module. It was found that the ion flux increased significantly during ECH injection. In the ECH injection period, the ion flux increased with the increasing impurity injection, which indicates the impurity ion components are enhanced by ionization in the D-module due to the application of ECH. During ECH injection period, the increase of the ion flux near the corner of the target plate shows a clear dependence on the gas species. The 2D visible emission has been captured by the high-speed camera and a bright emission near the corner of the target has been observed. The spectroscopic measurement in the D-module shows that the impurity ion emission increases remarkably during ECH injection. These results indicate the detached plasma change to the attached state.